2013
DOI: 10.4236/aim.2013.38a009
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Filamentous Fungi of Area from Brazilian Caatinga and High-Level Tannase Production Using Mango (<i>Mangifera indica</i> L.) and Surinam Cherry (<i>Eugenia uniflora</i> L.) Leaves under SSF

Abstract: Tannase is a biotechnologically important enzyme that can be produced during fungal fermentation of organic matter. The Caatinga is an exclusive Brazilian ecosystem that has been largely unexplored by science, particularly its filamentous fungal diversity. This study evaluated the diversity of filamentous fungi in the Caatinga soils of Pernambuco, Brazil, and their potential for tannase production by solid-state fermentation (SSF) of mango (Mangifera indica L.) and Surinam cherry (Eugenia uniflora L.) leaves. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
0
14
0
2
Order By: Relevance
“…This fact was already observed by Cruz et al (2013), who studied the diversity of fungi in the soil of the Parna Catimbau and identified 23 species of Aspergillus and 26 species of Penicillium. Unlike the present study, Cruz et al (2013) evaluated the diversity of filamentous fungi in only one area, analyzing the influence of seasonality on the community.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…This fact was already observed by Cruz et al (2013), who studied the diversity of fungi in the soil of the Parna Catimbau and identified 23 species of Aspergillus and 26 species of Penicillium. Unlike the present study, Cruz et al (2013) evaluated the diversity of filamentous fungi in only one area, analyzing the influence of seasonality on the community.…”
Section: Discussionmentioning
confidence: 61%
“…This fact was already observed by Cruz et al (2013), who studied the diversity of fungi in the soil of the Parna Catimbau and identified 23 species of Aspergillus and 26 species of Penicillium. Unlike the present study, Cruz et al (2013) evaluated the diversity of filamentous fungi in only one area, analyzing the influence of seasonality on the community. Oliveira et al (2013) carried out studies on the community of filamentous fungi in Catimbau Valley soils and identified 85 species of filamentous fungi, of which 28 belonged to the genus Aspergillus and 18 to the genus Penicillium, in contrast with the results found in the present study, in which Penicillium exhibited more species.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In a bibliographic survey conducted by Aguilar et al (2007), between the years 1969 to 2007, only five works are cited. A similar survey was conducted Solid state fermentation for the production of enzymes offers advantages over the conventional method of submerged fermentation (Pinto et al, 2005a;Cruz et al, 2013b). The means of production is simple: Agroindustrial by-products can be used, among the most common of which are grape skins, cashew fruit residue, coffee bean residue and bran of wheat, rice and oats, together with tannic acid (Lima et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last years, Oliveira et al, 46 and Cruz et al, 49 have reported some results that have increased our knowledge about mycological diversity in dry environments. Cruz et al, 49 noticed high abundance of the genus Penicillium and detected great richness values suggesting that a great number of species are adapted to low moisture content.…”
Section: -51mentioning
confidence: 99%